Anaerobic digestion of dry palms from five cultivars of Algerian date palm (Phoenix dactylifera L.) namely H'mira, Teggaza, Tinacer, Aghamou and Takarbouchet: A new comparative study. (15th April 2023) - Djaafri, Mohammed; Drissi, Aicha; Mehdaoui, Sabrina; Kalloum, Slimane; Atelge, M.R.; Khelafi, Mostefa; Kaidi, Kamel; Salem, Fethya; Tahri, Ahmed; Atabani, A.E.; Štěpanec, Libor
Abstract: The lignocellulosic properties of date palm waste (dry palm) differ significantly from one cultivar to another, which affects the anaerobic digestion (AD) process. This study is believed to be amongst the first to evaluate the influence of date palm cultivars on the biomethane yield in order to offer an annual, continuous and cost-effective biogas production model. In this work, 5 cultivars from date palm waste namely; H'mira (H), Teggaza (Tg), Tinacer (Ti), Aghamou (Ag) and Takarbouchet (Tk) were evaluated for biogas production. All experiments were performed for 45 days with 5 reactors in triplicate under mesophilic conditions (37 °C). The highest methane yield of 231.87 ml of CH4 /g of Volatile Solid (VS) was obtained with the Ag cultivars with a difference that varied between 37% and 62% depending on the cultivar type. These results indicate that the date palm cultivars massively influence the biomethane yield, it may give an opportunity for researchers to select the most suitable cultivars for methane production and provide opportunities to valorize other cultivars on other beneficial uses, such as adsorption, thermal insulation, or charcoal production etc. Graphical abstract: Image 1 Highlights: The biomethane yield is massively influenced by the date palm cultivars. The highest CH4 yield (231.87 ml CH4 /g VS) was obtained with the Aghamou (Ag) cultivar. The lowest CH4 yield (142.04 ml CH4 /g VS) was obtained with the Takarbouchet (Tk) cultivar. FTIR analyses confirm these findings with the highest transmittance (96.35%) with the Ag cultivar. This study allows to better perform techno-economic studies and helps to make correct decisions.